Investigation of Flexural Strength of African Copalwood (Daniella Oliveri) as Reinforcement in Concrete Slab - Abdulraheem, Kareem Kehinde; Jimoh, Abdullahi; Raji, Muktar Oladapo (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This study investigates the potential of African Copalwood as a reinforcing material in concrete slabs. The timber rods were randomly selected from the timber market because there is always variation in timber properties with position in stem, location and soil condition. Various test specimen were prepared according to the Code of practices BS EN 408:2003 using structural size specimens. Thirty (30) slabs of size 75 mm x 300 mm x 700 mm were cast in five sets (1 to 4%) for Timber-reinforced concrete slab (TRCS) and Steel-reinforced slab (SRS) with a mix ratio of 0.5:1:2:4 denoting water-cement ratio, cement, fine and coarse aggregate respectively. Longitudinal bars were varied in 1% to 4% slab cross-sectional area in different TRCS samples while the transverse bar was restricted to be 3% by standard and made constant in all the slab samples specimen. A 10 mm diameter steel bar is used as reinforcement in the SRS. Findings revealed that the mean failure stress for Tensile strength parallel to grain was 41.80 N/mm2, Bending strength parallel to grain was 37.05 N/mm2, Compression parallel to grain was 13.48 N/mm2, Compression perpendicular to grain was 8.88 N/mm2, Local Modulus of Elasticity (MOE) was 3800.17 N/mm2, Apparent MOE was 59.42 N/mm2. Also, with regards to TRCS, the flexural strength test at 28 days for 1% to 4% reinforcement in concrete slabs is 3.61, 5.29, 5.49 and 7.22 N/mm2 respectively. The SRS has a flexural strength of 11.54 N/mm2 at 87.5% composition in slabs. These findings indicate enhancement in the strength properties of the concrete slabs with the incorporation of the African Copalwood reinforcement.